Propaganda, polls, and public opinion: are the people manipulated? - Mitchell, Malcolm (Englewood Cliffs, N.J.: Prentice-Hall, 1977)
Defines propoganda and examines its uses and effects in society.
Bibliography: p. 116-118.
Filmography: p. 118-120.
Keywords: Propaganda; Public opinion; Advertising -- United States